1995
DOI: 10.1063/1.468819
|View full text |Cite
|
Sign up to set email alerts
|

Photoionization spectroscopy of the In–N2 van der Waals complex

Abstract: Vibronic structure of the cyclopentadienyl radical and its nonrigid van der Waals cluster with nitrogen A vibrationally resolved electronic spectrum is observed for the metal atom van der Waals complex In-N 2 . Two electronic band systems are detected with mass resolved two-color photoionization spectroscopy. A lower energy system is observed slightly to the blue of the In ͑ 2 D← P͒ atomic asymptote. It is characterized by a progression in the In-N 2 stretching mode with a frequency of e Јϭ76.7 cm Ϫ1 . The hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 54 publications
1
8
0
2
Order By: Relevance
“…In the case of [InN 2 ] + , a much higher fragmentation energy of 57.6 kJ mol À1 is obtained. [82] 5.1.5. Group 14 CNN can be generated by photolysis of NCN 3 in fluorohydrocarbon matrices.…”
Section: Group 13mentioning
confidence: 90%
See 1 more Smart Citation
“…In the case of [InN 2 ] + , a much higher fragmentation energy of 57.6 kJ mol À1 is obtained. [82] 5.1.5. Group 14 CNN can be generated by photolysis of NCN 3 in fluorohydrocarbon matrices.…”
Section: Group 13mentioning
confidence: 90%
“…The R2PI method has been used to study experimentally the [InN 2 ] + and [InN 2 ] complexes. [82] As anticipated, the results indicate that the bonding in [InN 2 ] + is much stronger than in [InN 2 ]. The (zero-field) ionization threshold of [InN 2 ] was determined to be 43 372 cm À1 (about 518.7 kJ mol À1 ).…”
Section: Group 13mentioning
confidence: 99%
“…81 Dies ist angesichts der Unterschiede der Dipolmomente und Polarisierbarkeiten von N 2 und NH 3 verständlich. Die R2PI‐Methode wurde für die experimentelle Untersuchung des [InN 2 ] + ‐ und [InN 2 ]‐Komplexes verwendet 82. Die Ergebnisse zeigen, dass die Bindung in [InN 2 ] + erwartungsgemäß viel stärker ist als in [InN 2 ].…”
Section: Distickstoff‐fixierung Durch Ligandenfreie Metallatomeunclassified
“…Demnach sind die Wechselwirkungen zwischen In und N 2 mit denen zwischen Ga und N 2 vergleichbar. Im Fall von [InN 2 ] + erhält man mit 57.6 kJ mol −1 eine viel höhere Fragmentierungsenergie 82…”
Section: Distickstoff‐fixierung Durch Ligandenfreie Metallatomeunclassified
“…Andrews and co-workers investigated Fe-N 2 , Sc-N 2 , Os-N 2 , and Ru-N 2 complexes with matrix-isolated infrared spectroscopy [12][13][14][15] and found that an Os atom can insert directly into the dinitrogen bond to form bent NOsN. Duncan and coworkers investigated In-N 2 and Al-N 2 complexes by photoionization spectroscopy, 16,17 and studied Mg + -N 2 , Ca + -N 2 , Nb + (N 2 ) n , and V + (N 2 ) n complexes using photodissociation spectroscopy. [18][19][20][21] Dagdigian and co-workers studied the electronic states of an Al-N 2 complex with laser-induced uorescence spectroscopy.…”
Section: Introductionmentioning
confidence: 99%